(untitled) (Bangladesh Journal of Otorhinolaryngology, 2025)
Persistent hyperparathyroidism (HPT) is defined as the development of hypercalcemia within 6 months of the first parathyroid operation, whereas hypercalcemia presenting after an interval of 6 months is termed recurrent HPT. A 43year old woman with persistent parathyroid adenoma with bilateral nephrocalcinosis following left lower parathyroidectomy. Initially, she was referred to a urologist for lower abdominal pain and urinary symptoms. Upon further evaluation, she was diagnosed with bilateral nephrocalcinosis, secondary to hypercalcemia caused by a left lower parathyroid adenoma. She underwent a left lower parathyroidectomy. Despite initial improvements, the patient’s PTH levels remained elevated during postoperative follow-up, indicating persistent hyperparathyroidism. Further imaging and biochemical investigations were performed, leading to the decision for a second surgery. A re-exploration of the neck was performed, during which the hyperfunctioning parathyroid tissue was identified and excised. Postoperatively, her PTH and calcium levels normalized. In this case the intra operative PTH level decreases more than 50% , and also frozen section biopsy showed positive for parathyroid tissue . There has been no post operative hypocalcemia is developed. Though PTH level initially within normal range but in post operative follow up 2 months after 2nd operation her S. PTH level was raised but normal calcium level. Bangladesh J Otorhinolaryngology 2024; 30 (2): 88-94